Sequential correction technique to avoid postoperative global coronal decompensation in rigid adult spinal deformity: a technical note and preliminary results - Bao, Hongda; Liu, Zhen; Zhang, Yuancheng; Sun, Xu; Jiang, Jun; Qian, Bangping; Mao, Saihu; Qiu, Yong; Zhu, Zezhang (European spine journal, 2019)
Purpose This study aims to evaluate this new sequential correction technique for preventing postoperative coronal imbalance. Methods Adult Spinal deformity (ASD) patients were stratifies into two types: primary thoracolumbar/lumbar (TL/L) curve with compensatory lumbosacral (LS) curve (Type I) and primary LS curve with compensatory TL/L curve (Type II): for Type I patients: correction of major TL/L curve and one- or two-level segmental rod installed at the convexity of the TL/L curve, L4-S1 TLIF to correct fractional curve and a short rod installed on the contralateral side and installation of long rods; for Type II patients: horizontalize L4 and L5, short rod installation at the convexity of the LS curve, distraction of curve with regional rod and installation of long rods. ASD patients were enrolled with inclusion criteria: with pre-op TL/L Cobb angle more than 30°, with pelvic fixation and with UIV over T10. Radiographic parameters were analyzed. Results Twenty-one patients were recruited (14 patients Type I and 7 Type II patients). Both Cobb angle and coronal offset were significantly improved after surgery. In Type I patients, Cobb angle was improved from 50.48° to 26.91° and coronal offset from 2.94 to 0.95 cm; in Type II patients, Cobb angle was improved from 61.42° to 28.48° and coronal offset from 2.82 to 1.38 cm. In the 10 patients with baseline coronal imbalance, 9 were corrected to coronal balance after surgery. Conclusion The sequential correction technique allows decomposing the complex correction surgery into several steps, and each step focuses only on one task. It can also reduce the difficulty of rod installation due to the separated maneuvers and multi-rod system. Level of evidence IV Graphic abstract These slides can be retrieved under Electronic Supplementary Material.